Strategi Kepemimpinan Kepala Sekolah dalam Pengembangan Profesionalisme Guru pada SMK Hutama - Zulfah, Habibah Nurhani; Nugroho, Dwi Sakti; Faqih, Irfan (UMSU, 2025)
This research aims to understand the implementation of school principal strategies in developing teacher professionalism at SMK Hutama. The background of this study is to build education for the future by assessing the professional performance of teachers. The research was conducted using a qualitative approach. Data sources are obtained from the principal and teachers of SMK Hutama through direct observation, interviews, and documentation. Data analysis employed qualitative data analysis methods. The findings from the study on the leadership strategies of the principal in developing teacher professionalism at SMK Hutama are (1) formulating a vision, mission, and both short-term and long-term goals to enhance teacher professionalism, (2) implementing school strategies by improving the work discipline of all school stakeholders, from students to parents, (3) conducting supervision to enhance the professional performance of teachers in teaching and learning activities, along with follow-up actions on school programs, and (4) fostering good cooperation with supervisors, foundations, parents, and government institutions.